2019
DOI: 10.3390/w11040838
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Unreported Benefits of Digital Water Metering: Literature Review and Expert Opinions

Abstract: Digital water meters can take Australian water utilities into the world of internet of things (IoT) and big data analytics. The potential is there for them to build more efficient processes, to enable new products and services to be offered, to defer expensive capital works, and for water conservation to be achieved. However, utilities are not mounting business cases with sufficient benefits to cover the project and operational costs. This study undertakes a literature review and interviews of industry experts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 49 publications
(130 reference statements)
1
43
0
Order By: Relevance
“…Overall, 67.5% agreed or strongly agreed with the benefits proposed, another 14.5% offered muted agreement while only 6% disagreed and 12% offered no opinion. The authors' previous literature review [41] identified sources of benefits of DWM, including the outcomes of academic research and reviews, which collectively reflect this strong level of support. Water savings and operational savings expressed by the experts were consistent with findings by researchers and practitioners in Australia [5,40] and overseas [6].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Overall, 67.5% agreed or strongly agreed with the benefits proposed, another 14.5% offered muted agreement while only 6% disagreed and 12% offered no opinion. The authors' previous literature review [41] identified sources of benefits of DWM, including the outcomes of academic research and reviews, which collectively reflect this strong level of support. Water savings and operational savings expressed by the experts were consistent with findings by researchers and practitioners in Australia [5,40] and overseas [6].…”
Section: Discussionmentioning
confidence: 84%
“…Insight into successful deployments are reported in published case studies, unpublished reports and local press reports [6,10,24,[32][33][34][35][36][37][38][39], as well as general reviews of DWM trials and implementations [11,40]. The literature review that preceded this study identified 75 benefits, many of them previously unreported, and catalogued them in a taxonomy [41]. Well-known benefits included identification of concealed leaks within properties, improved water balance analysis, meter reading cost savings, reduced mis-reads and estimated readings, reduced occupational health and safety issues, and more detailed water consumption data for network planning.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the benefit layer mainly contains four aspects including prolonging the asset life cycle, increasing energy sustainability, optimizing pressure and water quality, obtaining real-time water consumption shown in Figure 9 below. According to the benefits taxonomy by [71][72][73], the first two can be considered as business benefits while the third one belongs to shared benefits. The last benefit is classified as customer benefits.…”
Section: Benefit Layermentioning
confidence: 99%
“…To achieve these goals, we performed a systematic literature review in the field. Despite previous review studies having been conducted in this field [14][15][16][17][18][19][20][21][22][23], none-to the best of our knowledge-have been conducted from the perspective of ML and DA techniques. We believe that by providing a focused investigation of the literature, this review will benefit ML and DA practitioners as well as researchers in the water industry who are working on digital water metering and closely related fields.…”
Section: Introductionmentioning
confidence: 99%